Real-time PCR methods for identification and stability monitoring of Bifidobacterium longum subsp. longum UABl-14 during shelf life - Shehata, Hanan R.; Hassane, Basma; Newmaster, Steven G. (Frontiers in Microbiology, 2024)
Bifidobacterium longum subsp. longum UABl-14 ™ is an important probiotic strain that was found to support digestive health. Here we present the development and validation of real-time PCR methods for strain-specific identification and enumeration of this important strain. The identification method was evaluated for specificity using 22 target samples and 30 non-target samples. All target samples successfully amplified, while no amplification was observed from any non-target samples including other B. longum strains. The identification method was evaluated for sensitivity using three DNA dilution series and the limit of detection was 2 pg of DNA. Coupled with a viability dye, the method was further validated for quantitative use to enumerate viable cells of UABl-14. The viability dye treatment (PMAxx) was optimized, and a final concentration of 50 M was found as an effective concentration to inactivate DNA in dead cells from reacting in PCR. The reaction efficiency, linear dynamic range, repeatability, and reproducibility were also evaluated. The reaction efficiency was determined to be 97.2%, 95.2%, and 95.0% with R2 values of 99%, in three replicates. The linear dynamic range was 1.3102 to 1.3105 genomes. The relative standard deviation (RSD%) for repeatability ranged from 0.03 to 2.80, and for reproducibility ranged from 0.04 to 2.18. The ability of the validated enumeration method to monitor cell counts during shelf life was evaluated by determining the viable counts and total counts of strain UABl-14 in 18 multi-strain finished products. The viable counts were lower than label claims in seven products tested post-expiration and were higher than label claims in products tested pre-expiration, with a slight decrease in viable counts below label claim in three samples that were tested two to three months pre-expiration. Interestingly, the total counts of strain UABl-14 were consistently higher than label claims in all 18 products. Thus, the method enables strain-specific stability monitoring in finished products during shelf life, which can be difficult or impossible to achieve using the standard plate count method. The validated methods allow for simultaneous and cost-effective identification and enumeration of strain UABl-14 and represent an advancement in the quality control and quality assurance of probiotics.